The effects of exercise training on heart, brain and behavior, in the isoproterenol-induced cardiac infarct model in middle-aged female rats - Kata Tóth; Tamás Oroszi; Eddy A. van der Zee; Csaba Nyakas; Regien G. Schoemaker (Scientific Reports, 2022)
Abstract Women with cardiovascular disease may be more susceptible to concomitant mental health problems, such as depression and cognitive decline. Exercise training has beneficial effects on the cardiovascular system as well as on mental functions. Aim of the present study was to study the effects of exercise training on heart, brain and behavior in the isoproterenol (ISO) model in middle-aged female rats. Twelve months old female Wistar rats were submitted to ISO injections (70 mg/kg s.c., on two consecutive days) or received saline. One week later, rats were assigned to either exercise training (treadmill running) or control handling for five weeks. During the last 7 days, tests were performed regarding depressive-like behavior and cognitive function. Then, rats were sacrificed and heart and brains were dissected for (immuno)histochemistry. ISO-induced cardiac effects were eminent from cardiac fibrosis and declined cardiac function. Exercise training reversed cardiac damage and partly restored ISO-induced cardiac dysfunction. However, ISO treatment could not be associated with neuroinflammation, nor impaired hippocampal neurogenesis or neuronal function. Accordingly, no cognitive impairment or depressive-like behavior were observed. Actually, hippocampal microglia hyper-ramification was observed after ISO. Exercise left neuroinflammation and behavior merely unaltered, and even reduced neuronal function. Our data indicated that the cardiac damage after ISO in middle-aged female rats, and the subsequent beneficial effects of five weeks exercise training on the heart, were not reflected in changes in the brain nor in altered behavior.